2017
DOI: 10.3892/ijo.2017.4068
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of PTPRH (Sap-1) in colorectal tumors

Abstract: Tyrosine phosphorylation is one of the basic mechanisms for signal transduction in the cell. Receptors exhibiting tyrosine kinase activity are widely involved in carcinogenesis and are negatively regulated by receptor protein tyrosine phosphatases (RPTP). Genes encoding different RPTPs are affected by aberrant epigenetic regulation in cancer. PTPRH (SAP-1) has been previously described to be overexpressed in colorectal cancer (CRC) and classified as an oncogenic factor. Previous microarray-based mRNA expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…PTPRH protein is highly expressed in neuroblastomas, in association with tumor low stage and patient low risk, and PTPRH mRNA is induced in neuroblastoma cells upon retinoic acid differentiation ( Nunes-Xavier et al, 2019b ) ( Figure 2 ). These findings suggest a role for PTPRH in differentiation programs limiting neuroblastoma cell growth, and are consistent with the upregulation of PTPRH expression upon differentiation of other cell types ( Nunes-Xavier et al, 2012 ; Nunes-Xavier et al, 2013 ), as well as with its downregulation in some cancer types ( Nagano et al, 2003 ; Bujko et al, 2017 ). Remarkably, PTPRH was selected in a siRNA screening as a potential STAT3 regulator ( Parri et al, 2020 ), and it has also been found to associate with and dephosphorylate several RTK, including EGFR and IR ( Shintani et al, 2015 ; Yao et al, 2017 ).…”
Section: Classical Protein Tyrosine Phosphatases In Neuroblastomasupporting
confidence: 81%
“…PTPRH protein is highly expressed in neuroblastomas, in association with tumor low stage and patient low risk, and PTPRH mRNA is induced in neuroblastoma cells upon retinoic acid differentiation ( Nunes-Xavier et al, 2019b ) ( Figure 2 ). These findings suggest a role for PTPRH in differentiation programs limiting neuroblastoma cell growth, and are consistent with the upregulation of PTPRH expression upon differentiation of other cell types ( Nunes-Xavier et al, 2012 ; Nunes-Xavier et al, 2013 ), as well as with its downregulation in some cancer types ( Nagano et al, 2003 ; Bujko et al, 2017 ). Remarkably, PTPRH was selected in a siRNA screening as a potential STAT3 regulator ( Parri et al, 2020 ), and it has also been found to associate with and dephosphorylate several RTK, including EGFR and IR ( Shintani et al, 2015 ; Yao et al, 2017 ).…”
Section: Classical Protein Tyrosine Phosphatases In Neuroblastomasupporting
confidence: 81%
“…Interestingly, when comparing mutant lincRNA- Cox2 -specific DE genes, there are only six that overlap between the spleen and lung (Figure 6M). Of these six genes, only one gene changed from being upregulated to downregulated from the spleen to the lung, Ptprh (synonym Sap-1) (Figure S7C; Bujko et al, 2017). Database for Annotation, Visualization, and Integrated Discovery (DAVID) analysis of the differentially expressed genes of the spleen and lung show similar pathways, such as glycoprotein and inflammatory response, as well distinct pathways, such as fibronectin and heparin binding in the spleen or cellular homeostasis and secretory granule pathways in the lung (Figures S7A and S7B).…”
Section: Resultsmentioning
confidence: 99%
“…We provided evidence here that the protein tyrosine phosphatase receptor type H, encoded by PTPRH (also known as SAP-1) is expressed at lower levels in the tumors of patients treated with trastuzumab and among the genes most differentially expressed in the primary tumors of patients treated with trastuzumab. Thus, administration of trastuzumab in patients with breast cancer is associated with decreased primary tumor expression of a molecule whose depletion results in activation of epidermal growth factor receptor signaling 7 , expressed at lower levels in colorectal cancer 5 and whose deficiency defines a high-risk phenotype in pediatric solid tumors 6 . Table 1: PTPRH is differentially expressed in the primary tumors of breast cancer patients treated with trastuzumab.…”
Section: Discussionmentioning
confidence: 99%